2020
DOI: 10.3348/jksr.2020.81.4.965
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Intraosseous Hibernoma: A Case Report and Review of Literature

Abstract: Hibernoma is a rare benign tumor that arises from vestiges of brown fat. Spinal intraosseous hibernoma has only recently been described in the literature, and only 12 cases have been reported to date due to its extreme rarity. Here, we report the case of a patient who was incidentally diagnosed with an intraosseous hibernoma in the thoracic spine, following a diverse imaging work-up and pathologic confirmation. We correlate the clinical presentation and imaging features of our case with those of previously rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…However, included in this series is the first reported paediatric case in a 7‐year‐old child, while the youngest patient previously reported was 35 31 . The patients in our study showed an almost even distribution between females and males; however, the aggregate of prior investigations has shown a strong female predominance 8–31 . Cancer‐related work‐up/surveillance or pain were the most common indications for imaging, similar to prior reports.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…However, included in this series is the first reported paediatric case in a 7‐year‐old child, while the youngest patient previously reported was 35 31 . The patients in our study showed an almost even distribution between females and males; however, the aggregate of prior investigations has shown a strong female predominance 8–31 . Cancer‐related work‐up/surveillance or pain were the most common indications for imaging, similar to prior reports.…”
Section: Discussionsupporting
confidence: 84%
“…Intraosseous hibernomas are rarely documented, usually in the form of case reports or small series, with only 38 cases in the English language literature 8–31 . The relatively small number of reported cases limits our understanding of these tumours.…”
Section: Introductionmentioning
confidence: 99%
“…The first known case of an intraosseous aggregate of brown adipose tissue was discovered during a trephine bone biopsy as part of a clinical work-up for essential thrombocytopenia in 2006 [7] . Currently, only 35 total cases of intraosseous hibernomas have been reported within international literature [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] . Similar to their soft tissue counterparts, they are usually found incidentally while working up a different clinical scenario, although occasionally they present with pain.…”
Section: Introductionmentioning
confidence: 99%